Управління професійним становленням майбутнього менеджера на початковому етапі університетської освіти - Бабенко, І. В.; Babenko, I. V. (Видавництво Львівської політехніки, 2023)
У статті здійснено аналіз структури процесу професійного становлення майбутніх менеджерів, визначено складові характеристик майбутнього фахівця, що забезпечують ефективне управління професійним становленням. Схарактеризовано зміст навчальної дисципліни "Університетська освіта та академічне письмо" як важливої складової управлінського процесу професійного становлення майбутніх менеджерів. На основі аналізу літературних джерел визначено критерії професійного становлення студента.

The article analyzes the structure of the process of professional formation of future managers, identifies the components of the characteristics of a future specialist that ensure effective management of professional formation. The concept of professional formation of the individual, which is considered by scientists as the formation of professional orientation, competence, socially significant and professionally important qualities and their integration, readiness for constant personal and professional growth, is defined. The main directions of professionalization are singled out: professional training, professional self-determination, self-affirmation and self-improvement, development of intellectual potential in the field of professional activity, spiritual, aesthetic and moral development. The initial stage of university education should provide future managers with basic theoretical knowledge about the analysis of management phenomena, develop the skills and abilities inherent in this process, thinking and a creative approach to business, and ensure the formation of a professional worldview. The content of the academic discipline "University education and academic writing" is characterized as an important component of the management process of professional development of future managers. The content modules of the discipline "Content of professional training in higher education", "Academic writing as a type of academic (scientific) communication" were analyzed. They ensure in the first years of studying at the university that students form a system of knowledge about the specifics of a manager’s professional activity, typical tasks of his activity, development of skills in planning a system of activities aimed at supporting academic integrity, which is the basis of the functioning of any educational institution. Based on the analysis of literary sources, the criteria for a student’s professional development have been determined: awareness of the goals of professional activity, the desire to know one’s business, to master all professional functions; assimilation of basic knowledge, requirements of the profession for a specialist, awareness of one’s capabilities; readiness for the practical realization of the set professional goals, the search for one’s own individual style, optimization of the process of business communication, free performance of professional activities, professional improvement, mastery and creativity.
Management of the professional development of the future manager at the initial stage of university education
Keywords: професійне становлення; менеджер; університетська освіта; академічне письмо; управління; професійна підготовка; компетентності; фахова компетентність; professional development; manager; university education; academic writing; management; professional training; competences; professional competence; 378.04; 005.95-051